Bacterial etiology and antibiotic resistance pattern of adult pneumonia in South Asia: a review - Eusra, Kazi Fatiha; Shehrin, Shaira (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.